Government–Business Relations and Corporate Cash Holdings: Evidence from China. (16th January 2023) - Gao, Yu; Cai, Yan; Teng, Zhuoqi; Fang, Yuantao
Abstract: This study employs data from Chinese firms between 2017 and 2019 to explore how government–business relations affect corporate cash holdings. We find that healthy government–business relations have a significantly positive impact on corporate cash holdings. The mechanism test reveals that the former affects the latter via investment opportunities. Furthermore, product market competition positively moderates the relationship between government–business relations and corporate cash holdings, but financial constraints negatively moderate this relationship. The results of our research have implications for the government to optimize the quality of governance and for enterprises to adjust their business strategies.